2016
DOI: 10.1073/pnas.1517259113
|View full text |Cite
|
Sign up to set email alerts
|

Extended synaptotagmins are Ca 2+ -dependent lipid transfer proteins at membrane contact sites

Abstract: Organelles are in constant communication with each other through exchange of proteins (mediated by trafficking vesicles) and lipids [mediated by both trafficking vesicles and lipid transfer proteins (LTPs)]. It has long been known that vesicle trafficking can be tightly regulated by the second messenger Ca 2+ , allowing membrane protein transport to be adjusted according to physiological demands. However, it remains unclear whether LTP-mediated lipid transport can also be regulated by Ca 2+ . In this work, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(177 citation statements)
references
References 48 publications
10
167
0
Order By: Relevance
“…It has been reported that other TULIP-domain proteins bind and transport lipids (5, 40, 42), suggesting that TMEM24 might as well. To identify potential lipid ligands for TMEM24, we overexpressed its SMP domain in mammalian cells (Expi293) and used mass spectrometry to identify lipids that copurify with it.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that other TULIP-domain proteins bind and transport lipids (5, 40, 42), suggesting that TMEM24 might as well. To identify potential lipid ligands for TMEM24, we overexpressed its SMP domain in mammalian cells (Expi293) and used mass spectrometry to identify lipids that copurify with it.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to these processes, lipid transfer reactions can be observed with single proteins 4, 21. More complex reconstitutions have now been carried out with contact site bridging by membrane receptors [58], countercurrent generation by PI 4-phosphatase [37], and Ca 2+ -induced lipid transport 15, 59. For lipid countercurrents, it is clear that LTPs such as ORPs preferentially unload their first ligand when the second ligand is available in the acceptor membrane [31].
In Vitro Reconstitution Approaches: Lessons from SNARE-Dependent Membrane Fusion

The complexity of a living cell can hardly be matched by an in vitro reconstitution.

…”
Section: Approaches To Study Lipid Transfer By Ltpsmentioning
confidence: 99%
“…ER-PM tethering can also be mediated by numerous lipid transfer proteins. ER-localized E-Syts engage PI(4,5)P 2 on the PM via their C2 domains [37], and their SMP domain is shown to be a lipid transfer module [38][39][40]. Such interactions are thought to be sensitive to the levels of cytosolic Ca 2+ [41].…”
Section: Er-pm Contact Sitesmentioning
confidence: 99%